Preparation and photoluminescence characteristics of In(OH) 3:xTb3+ obtained by Microwave-Assisted Hydrothermal method - Motta, F. V.; Marques, A. P A; Li, M. S.; Abreu, M. F C; Paskocimas, C. A.; Bomio, M. R D; Souza, R. P.; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier, 2013)
Crystalline terbium-doped indium hydroxide structures were prepared by a rapid and efficient Microwave-Assisted Hydrothermal (MAH) method. Nanostructures were obtained at a low temperature. FE-SEM images confirm that these samples are composed of 3D nanostructures. XRD, optical diffuse reflectance and photoluminescence (PL) measurements were used to characterize the products. Emission spectra of terbium-doped indium hydroxide (In(OH)3:xTb 3+) samples under excitation (350.7 nm) presented broad band emission referent to the indium hydroxide matrix and 5D4 → 7F6, 5D4 → 7F 5, 5D4 → 7F4, and 5D4 → 7F3 terbium transitions at 495, 550, 590 and 627 nm, respectively. Relative intensities of the Tb 3+ emissions increased as the concentration of this ion increased from 0, 1, 2, 4 and 8 mol%, of Tb3+, but the luminescence is drastically quenched for the In(OH)3 matrix. © 2012 Elsevier B.V. All rights reserved.
Keywords: Indium hydroxide; Microwave-Assisted Hydrothermal; Terbium; Broadband emission; Diffuse reflectance; Emission spectrums; Hydrothermal methods; Low temperatures; Microwave-assisted; Photoluminescence characteristics; Photoluminescence measurements; Relative intensity; XRD; Emission spectroscopy; Nanostructures; Photoluminescence; Indium